Surface and coherent contributions of plasmon fields to ultraviolet tip-enhanced coherent anti-Stokes Raman scattering. (10th July 2020) - Feng, Yanting; Gao, Man; Wang, Yu; Yang, Zhilin; Meng, Lingyan
Abstract: Design of plasmonic substrates is of immense importance for high sensitivity and spatial resolution in plasmon-enhanced spectroscopy. In this study, the enhancement factors (EFs) of tip-enhanced coherent anti-Stokes Raman scattering (TECARS) contributed by surface and quantum coherent effects in the ultraviolet region are theoretically analyzed using three-dimensional finite-difference time-domain (3D-FDTD) method. In the multi-resonant TECARS configuration, surface and coherent EFs of 10 18 and 10 9, respectively, can be achieved by considering the synthetic effect of surface and coherent enhancement mechanisms, providing the total TECARS EF of 10 27 and sub-5 nm spatial resolution. Our theoretical results not only provide a deeper understanding of ultraviolet (UV)-TECARS but also can be used as a highly efficient reference for the experimental design of TECARS platform.